2002
DOI: 10.1016/s0960-9822(02)01107-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Nir2 to Lipid Droplets Is Regulated by a Specific Threonine Residue within Its PI-Transfer Domain

Abstract: Nir2, like its Drosophila homolog retinal degeneration B (RdgB), contains an N-terminal phosphatidylinositol-transfer protein (PI-TP)-like domain. Previous studies have suggested that RdgB plays an important role in the fly phototransduction cascade and that its PI-transfer domain is critical for this function. In this domain, a specific mutation, T59E, induces a dominant retinal degeneration phenotype. Here we show that a similar mutation, T59E in the human Nir2 protein, targets Nir2 to spherical cytosolic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 24 publications
2
37
1
Order By: Relevance
“…using indirect immunofluorescence and confocal microscopy analysis. OSBP ( Figure 3A), CERT ( Figure 3B), and Nir2 ( Figure 3C) were localized mainly to the Golgi complex of control cells, consistent with previous reports (Storey et al, 1998;Litvak et al, 2002), and treatment with 25OH markedly enhanced their Golgi association, as determined by colocalization with Golgi markers. This treatment also enhanced their interaction with VAPs as demonstrated by coimmunoprecipitation studies ( Figure 3D).…”
Section: Depletion Of Vaps Affects the Golgi Targeting Of Nir2 Osbpsupporting
confidence: 91%
“…using indirect immunofluorescence and confocal microscopy analysis. OSBP ( Figure 3A), CERT ( Figure 3B), and Nir2 ( Figure 3C) were localized mainly to the Golgi complex of control cells, consistent with previous reports (Storey et al, 1998;Litvak et al, 2002), and treatment with 25OH markedly enhanced their Golgi association, as determined by colocalization with Golgi markers. This treatment also enhanced their interaction with VAPs as demonstrated by coimmunoprecipitation studies ( Figure 3D).…”
Section: Depletion Of Vaps Affects the Golgi Targeting Of Nir2 Osbpsupporting
confidence: 91%
“…We have previously shown that Nir2 mainly localizes in the Golgi apparatus, but it is also found in the ER in interphase cells (36). To determine the localization of VAP-B in HeLa cells, we used the anti-VAP-B antibody in indirect immunofluorescence and confocal microscopy analyses.…”
Section: Nirs Interact With Vap-b Via Their Conserved Ffat Motif-mentioning
confidence: 99%
“…Nir2 is not an integral, membrane-spanning protein but is associated to Golgi/endoplasmatic reticulum membranes. A T59E mutation in Nir2 changed the cellular localization to spherical cytosolic lipid droplets [30]. It is suggested that phosphorylation of Thr59 and relocalization of Nir2 is stimulated by incubation with oleic acid.…”
Section: Phosphorylation Of Pi-tpa and Pi-tpb In Vitro And In Vivomentioning
confidence: 99%